2021
DOI: 10.3390/v13061183
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Bio-Layer Interferometry-Based Protease Assay Using HIV-1 Protease as a Model

Abstract: Proteolytic enzymes have great significance in medicine and the pharmaceutical industry and are applied in multiple fields of life sciences. Therefore, cost-efficient, reliable and sensitive real-time monitoring methods are highly desirable to measure protease activity. In this paper, we describe the development of a new experimental approach for investigation of proteolytic enzymes. The method was designed by the combination of recombinant fusion protein substrates and bio-layer interferometry (BLI). The prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Support for the PR/MA-CA polyprotein ternary complex (Figure 1D) comes from small-angle neutron scattering experiments on a Gag polyprotein in which the MA and CA subdomains were found to be closely associated [33], while solution NMR studies of a Gag MA-CA polyprotein revealed that the MA and CA subdomains aligned with complementary surfaces and charges to within 2-6 A in three models [34]. The published experimental results on PR binding to Gag cleavage sites [23][24][25], and Gag MA and CA subdomains associations [33,34] support the structure-based model of HIV-1 PR bound to the MA-CA polyprotein in Figure 1D [23]. The HIV-1 PR S-groove [22], ribbon backbone with subdomains indicated left-to-right (MA yellow 1L6N.pdb, CA bronze 1L6N.pdb and 4XFX.pdb, NC yellow 1MFS.pdb, p6 bronze 2C55.pdb as modified [22]), SP1 and SP2 regions in black, five Gag cleavage sites indicated as are the non-cleavage site residues MA L75, CA H219, and NC R409, which when mutated resulted in PI resistance (carbon grey, nitrogen blue) [30].…”
Section: Introductionmentioning
confidence: 85%
See 4 more Smart Citations
“…Support for the PR/MA-CA polyprotein ternary complex (Figure 1D) comes from small-angle neutron scattering experiments on a Gag polyprotein in which the MA and CA subdomains were found to be closely associated [33], while solution NMR studies of a Gag MA-CA polyprotein revealed that the MA and CA subdomains aligned with complementary surfaces and charges to within 2-6 A in three models [34]. The published experimental results on PR binding to Gag cleavage sites [23][24][25], and Gag MA and CA subdomains associations [33,34] support the structure-based model of HIV-1 PR bound to the MA-CA polyprotein in Figure 1D [23]. The HIV-1 PR S-groove [22], ribbon backbone with subdomains indicated left-to-right (MA yellow 1L6N.pdb, CA bronze 1L6N.pdb and 4XFX.pdb, NC yellow 1MFS.pdb, p6 bronze 2C55.pdb as modified [22]), SP1 and SP2 regions in black, five Gag cleavage sites indicated as are the non-cleavage site residues MA L75, CA H219, and NC R409, which when mutated resulted in PI resistance (carbon grey, nitrogen blue) [30].…”
Section: Introductionmentioning
confidence: 85%
“…Support for the PR/MA-CA polyprotein ternary complex (Figure 1D) comes from small-angle neutron scattering experiments on a Gag polyprotein in which the MA and CA subdomains were found to be closely associated [33], while solution NMR studies of a Gag MA-CA polyprotein revealed that the MA and CA subdomains aligned with complementary surfaces and charges to within 2-6 A in three models [34]. The published experimental results on PR binding to Gag cleavage sites [23][24][25], and Gag MA and CA subdomains associations [33,34] support the structure-based model of HIV-1 PR bound to the MA-CA polyprotein in Figure 1D [23]. The HIV-1 PR S-groove model was then expanded to include many other retroviral proteases where the native multi-drug resistance was found to be due to a combination of primary active site mutations and secondary S-groove mutations [22].…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations